A Framework for Purchasing Health Care Labor - Zurn, Pascal (World Bank, Washington, DC, 2013)
Health care labor is central to managing and delivering health services. Because recruitment and retention policies are key issues for purchasers, gaining insights into labor-purchasing mechanisms may permit them to be addressed more effectively. This paper is intended to provide a brief introduction to health care labor purchasing and the mechanisms through which it can have an impact on the delivery of health services and on health system performance. A framework is developed to foster understanding of health labor purchasing mechanisms. This framework examines the different types and characteristics of the purchasers and providers. It also examines the terms of labor purchasing, that is, working conditions (career development, contract duration, working time and shift work, work autonomy and separation), remuneration and benefits. These elements determine, to a large extent, workers' behavioral responses such as willingness to apply for and accept employment and job satisfaction. In turn, these behavioral responses are likely to affect performance. Finally, contextual and policy factors related to the health care system and the labor market that affect labor purchasing, health services delivery, and health system performance, are also considered in the framework. Under this category, we review the public-private mix, the purchaser-provider split, contracting in and out, purchaser power, and provider power. The framework presented in this paper encompasses a wide diversity of elements, but the role of yet more factors should also be investigated. For instance, the role of cultural or political factors is likely to affect labor purchasing. The effects of migration on labor purchasing should also be considered. A better understanding of the interaction between the elements of the framework would reinforce the analysis.